2010
DOI: 10.1016/j.gloplacha.2010.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and hydrologic variability in the East China Sea during the last 7000years based on oxygen isotope records of the submarine cavernicolous micro-bivalve Carditella iejimensis

Abstract: a b s t r a c tThe micro-bivalve Carditella iejimensis inhabits the sediment surface within submarine caves at Ie Island, Okinawa, Japan. A comparison of the δ 18 O values (δ 18 O aragonite ) of empty and living shells indicates that the shell is formed over several seasons, and that the main cause of mortality is low water temperature. According to this hypothesis, it is likely that the shells with heaviest δ 18 O aragonite values (− 0.4‰) among the recent dataset formed under or close to the lower limit of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…years BP was related to an intensification of the winter monsoon, although they reported no changes in temperatures or salinities during the past 2700 years. Yamamoto et al (2010) Kitamura et al (2013) confirmed that no changes have occurred in either sea-surface temperatures or salinities during the past 7000 years. These results are consistent with the findings of previous studies in the East China Sea (Jian et al, 2000;Ijiri et al, 2005;Sun et al, 2005;Lin et al, 2006;Kubota et al, 2010).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…years BP was related to an intensification of the winter monsoon, although they reported no changes in temperatures or salinities during the past 2700 years. Yamamoto et al (2010) Kitamura et al (2013) confirmed that no changes have occurred in either sea-surface temperatures or salinities during the past 7000 years. These results are consistent with the findings of previous studies in the East China Sea (Jian et al, 2000;Ijiri et al, 2005;Sun et al, 2005;Lin et al, 2006;Kubota et al, 2010).…”
Section: Discussionmentioning
confidence: 66%
“…1a), are among the northernmost sites at which P. taniguchii has been found. According to Yamamoto et al (2010), seasonal changes in water temperature in Daidokutsu Cave range from 29 uC in August-September to 21 uC in February. Data from the Japan Oceanographic Data Center (2007) show that, at water depths of 20 m, similar to those of the study area, water temperatures range from 28.2 6 0.6 uC in September to 22.0 6 0.9 uC in February, which indicates that P. taniguchii can survive at temperature of 21 uC during the winter season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no records of Holocene SSTs for the Okinawa Islands based on coral proxies, because well preserved fossil corals (in situ occurrences and no diagenetic alternation) have not been found. Kitamura et al (2007) and Yamamoto et al (2008Yamamoto et al ( , 2010 analyzed δ 18 O values of empty (dead) whole shells (δ 18 O shell ) of the marine cave-dwelling microbivalve Carditella iejimensis ( Figure 1c) collected from cored sediments in the submarine cave Daidokutsu (meaning 'large cave' in Japanese) at 29-m water depth off Okinawa Island (26°43′N, 127°44′E) (Figure 1c, d). Carditella iejimensis shells are less than 3.5 mm in height and length, and the species inhabits the sediment surface.…”
Section: Introductionmentioning
confidence: 99%
“…Mollusk shells have been shown to be faithful environmental archives (Goodwin et al, 2001;Carré et al, 2005;Schöne et al, 2005;Lazareth et al, 2006;Yamamoto et al, 2010;Batenburg et al, 2011;Carré et al, 2012a;Sadler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%